Executive Function Training Improves Emotional Competence for Preschool Children: The Roles of Inhibition Control and Working Memory - Li, Quan; Liu, Peiwei; Yan, Ni; Feng, Tingyong (Frontiers in Psychology, 2020)
The study examined how executive function (EF) training could improve children’s emotional competence (EC). Children (N = 55; Mage = 50.64 months) were assigned into two groups, namely the EF training group and the no-training group. The present study attempted to use a 2 (group: EF training VS no-training) × 2 (test time: pretest VS post-test) between-and- within-subjects experimental design to investigate the effect of EF training on the improvement of EC for 4-year-old children. Results showed that, (1) children in EF training group had significantly higher scores on EC than that of no-training group; (2) The change of inhibition control and working memory could significantly predict their variation of EC. These results suggested that the improvement of EC caused by EF training could be linked to the ability of inhibition control and working memory.